Fluvial facies, vertebrate taphonomy and palaeosols of the Teekloof formation (Permian) near Beaufort West, Cape Province, South Africa - Smith, Roger M H (Department of Geological Sciences, 2017)
The main Karoo Basin of South Africa contains a relatively continuous sequence of continental deposits that accumulated over a 100 million year period from Permo-Carboniferous (280 Ma) to early Jurassic (180 Ma). In the southwestern region of the basin the Karoo succession is approximately 4 000 m thick, the upper half of which consists of vertebrate fossil-bearing fluvial rocks of the Beaufort Group. This study deals with Lower Beaufort (Adelaide Subgroup) strata belonging to the Teekloof Formation which are exposed in the cast-west trending erosional escarpment between the towns of Beaufort West and Fraserburg in the central Cape Province. The 450-mctre succession consists mainly of vertically accreted floodplain mudrocks with interbedded continuous sheets of fine-grained sandstone that bear evidence of having accumulated by lateral accretion on the inner banks of meandering channels. The mudrocks contain numerous fossilized skeletons of therapsid "mammal-like" reptiles as well as more primitive cotylosaurs and a few amphibians. Rarely, impressions of Glossopteris leaves and equisetalcan stems are found although root moulds are relatively abundant. Several types of calcareous nodules and sheets occur in the mudrocks and arc interpreted as evidence of calcic palaeosols that formed under semi-arid climatic conditions. This is an interdisciplinary study that integrates a conventional sedimentary facies analysis with investigations of the taphonomy of in situ therapsid fossils and the nature and distribution of palaeosols. Such an approach has not previously been applied to any of the Karoo strata. The results contain descriptive and quantitative information on sedimentary processes, palaeohydrology, absolute time represented in the stratigraphic record and the topography, soils and habitats of the ancient landscape. These are summarized into a palaeoenvironmental synthesis of the Teckloof Formation.